PENGARUH PERTUMBUHAN EKONOMI, UMP, DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA DI JAWA BARAT - Hikmawati, Selvi Nur; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p18, 2024)
The purpose of this study was to analyze the effect of economic growth, UMP, and education level simultaneously and partially on employment in West Java Province. This study uses secondary data obtained from the BPS of West Java Province in the time span from 2005-2019 (15 years), with 15 observation points. The method of data collection in this study is the non-participant observation method. The analysis technique used is multiple linear regression analysis. The results showed that economic growth, UMP, and level of education simultaneously had a significant effect on employment. Economic growth, UMP, and level of education partially have a positive and significant effect on employment. Education level is a variable that has a dominant influence on employment.